Neutrophil / Lymphocyte Ratio is not Correlated with Disease Activity in Rheumatoid Arthritis Patients - Ehab M. Mikhael; Turath N.Ibrahim (College of Pharmacy University of Baghdad, 2017)
Rheumatoid arthritis is a chronic systemic inflammatory disease. Inflammation leads to joint damage and increases the risk of cardiovascular diseases. Neutrophil lymphocyte ratio (NLR) is a measure of inflammation in many diseases. Therefore, we aimed to evaluate the usefulness of NLR to detect inflammation in RA, and its correlation to RA disease activity indices and some hematological parameters. A cross-sectional study involving 24 patients with active rheumatoid arthritis (RA) who are using MTX participated in this study. All patients were clinically evaluated using disease activity score of 28 joints (DAS28) and simplified disease activity index (SDAI), whereas functional disability was assessed by health assessment questionnaire disability index (HAQDI); Moreover, blood specimen of each patient was used for measuring erythrocyte sedimentation rate (ESR), C â€" reactive protein (CRP), rheumatoid factor (RF), hemoglobin (Hb), white blood cells (WBC) count, platelets and red blood cells (RBCs) count, and NLR ratio.NLR was positively correlated with ESR and inversely correlated with Hb, but it didnâ€™t show any correlation with other clinical and laboratory parameters. In conclusion NLR is less correlated with inflammation and not suitable to monitor disease activity in RA patients using MTX. Keywords: Rheumatoid arthritis, Inflammation, Neutrophil lymphocyte ratio.